2016
DOI: 10.2337/db16-0426
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of PPARα With the Canonic Wnt Pathway in the Regulation of Renal Fibrosis

Abstract: Peroxisome proliferator–activated receptor-α (PPARα) displays renoprotective effects with an unclear mechanism. Aberrant activation of the canonical Wnt pathway plays a key role in renal fibrosis. Renal levels of PPARα were downregulated in both type 1 and type 2 diabetes models. The PPARα agonist fenofibrate and overexpression of PPARα both attenuated the expression of fibrotic factors, and suppressed high glucose–induced or Wnt3a-induced Wnt signaling in renal cells. Fenofibrate inhibited Wnt signaling in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 49 publications
3
36
0
Order By: Relevance
“…FA, a PPARα agonist, has shown antiangiogenic effects in PDR patients and in several NV animal models including VKO mice . Our previous study reported that FA inhibited the Wnt signaling pathway . The present study indicated that FA significantly decreased mitochondrial biogenesis and ROS production in isolated EPCs in vitro (Figs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…FA, a PPARα agonist, has shown antiangiogenic effects in PDR patients and in several NV animal models including VKO mice . Our previous study reported that FA inhibited the Wnt signaling pathway . The present study indicated that FA significantly decreased mitochondrial biogenesis and ROS production in isolated EPCs in vitro (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…Dysregulation of Wnt signaling is an important cause of impaired mitochondrial biogenesis and reactive oxygen species (ROS) generation, leading to exacerbated pathologic outcomes in tumor development and abnormal NV . Several studies have reported that the Wnt signaling pathway regulates NV in the development of ocular diseases . In 2013, our group reported that the aberrant activation of the Wnt pathway played an important role in hypoxia‐induced EPC release using the oxygen‐induced retinopathy mouse model .…”
Section: Introductionmentioning
confidence: 99%
“…Cells from a human renal tubular epithelial cell line (HK‐2) were purchased from the ATCC and cultured with DMEM containing 10% foetal bovine serum (Gibco, Life Technologies). Cells were infected with lentivirus particles harbouring CCNG2 or control GFP lentivirus (GeneChem) and divided into high‐glucose (HG; 30 mmol/L d ‐glucose) and low‐glucose (LG; 5.5 mmol/L d ‐glucose and 24.5 mmol/L l ‐glucose) treatment groups (Figure ) . Cells were starved by incubation in DMEM containing 1% serum for 24 hours, and then, the media was replaced with DMEM containing 10% serum and the indicated concentrations of glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were infected with lentivirus particles harbouring CCNG2 or control GFP lentivirus (GeneChem) and divided into high-glucose (HG; 30 mmol/L d-glucose) and low-glucose (LG; 5.5 mmol/L d-glucose and 24.5 mmol/L l-glucose) treatment groups ( Figure S2). 37,38 Cells were starved by incubation in DMEM containing 1% serum for 24 hours, and then, the media was replaced with DMEM containing 10% serum and the indicated concentrations of glucose. Cells were infected with lentivirus particles harbouring CCNG2 and exposed to the Wnt signalling activator CHIR99021 (1 mmol/L; R&D Systems; 4423) or an equivalent volume of DMSO in DMEM (negative control) for 72 hours.…”
Section: Cell Culture Transfection and Treatmentmentioning
confidence: 99%
“…However, previous studies have shown that the protective effect of FF against DN can be independent of its lipid-lowering effect [11,12] . FF also has renal protective effects in a model of type 1 diabetes (T1D), which are achieved through activation of the transforming growth factor (TGF)-β1/smad3 and canonical Wnt pathways that ameliorate renal fibrosis [13,14] . However, the underlying mechanisms of the renal protective effects of FF in T1D have not been fully investigated.…”
Section: Ivyspringmentioning
confidence: 99%